2017
DOI: 10.1186/s13643-017-0457-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, behavioural and pharmacogenomic factors influencing the response to levothyroxine therapy in patients with primary hypothyroidism—protocol for a systematic review

Abstract: BackgroundSuboptimal thyroid hormone therapy including under-replacement and over-replacement is common amongst patients with hypothyroidism. This is a significant health concern as affected patients are at risk of adverse cardiovascular or metabolic consequences. Despite a growing body of evidence on the effects of various factors on thyroid hormone replacement, a systematic appraisal of the evidence is lacking. This review aims to appraise and quantify the extent to which clinical, behavioural and pharmacoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 24 publications
0
12
0
1
Order By: Relevance
“…Hypothyroidism is also associated with decreased quality of life, most likely related to symptoms such as changes in body weight, fatigue, weakness and depression [1, 12, 1719]. Physicians and patients themselves rate fatigue and emotional susceptibility as being particularly relevant to the impact of hypothyroidism [51].…”
Section: Hypothyroidism In Contextmentioning
confidence: 99%
See 3 more Smart Citations
“…Hypothyroidism is also associated with decreased quality of life, most likely related to symptoms such as changes in body weight, fatigue, weakness and depression [1, 12, 1719]. Physicians and patients themselves rate fatigue and emotional susceptibility as being particularly relevant to the impact of hypothyroidism [51].…”
Section: Hypothyroidism In Contextmentioning
confidence: 99%
“…Despite the switch to levothyroxine monotherapy in the 1970s [65], the need for combination therapy with levothyroxine + LT3 has been recently readdressed in several clinical guidelines [13, 75, 76]. More than a third of patients remain inadequately treated despite levothyroxine therapy, with evidently elevated TSH levels and/or persistent symptoms [12, 13]. Even when TSH levels are controlled on levothyroxine, about 5–10% of treated hypothyroid patients have persistent symptoms for various reasons [76], including differences in individual set-points, coexistence of other autoimmune diseases, and failure to appropriately convert T4 to T3 with a low T3/T4 ratio, on levothyroxine monotherapy.…”
Section: Unresolved Issues In Hypothyroidism Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…While medical therapy with an anti-thyroid drug is commonly adopted in European nations and Japan as the first-choice method of therapy, the disease still often occurs. Recent systematic review reported the clinical, behavioral and pharmacogenomic factors could be influence in response to levothyroxine therapy in patients with primary hypothyroidism (Dew et al, 2017).…”
Section: Discussionmentioning
confidence: 99%